МӘНАЎИЙ МИЙРАС – ЖӘМИЙЕТ ТИРЕГИ - Утамбетова, А.; Шавкатова, М. (ILIM hám JÁMIYET, 2017)
The article is devoted to the study of spiritual heritage, moral norms of behaviour, that is a part of cultural heritage, and traditions, customs and holidays of the Karakalpak people.